A ratiometric nanoprobe based on carboxylated graphitic carbon nitride nanosheets and Eu3+ for the detection of tetracyclines. Issue 3 (21st December 2020) - Ti, Mengru; Li, Yasi; Li, Zhongqiu; Zhao, Dongxu; Wu, Li; Yuan, Longfei; He, Yujian
Abstract : A convenient and rapid method that combines a fluorescent nanoprobe based on C-g-C3 N4 -Eu 3+ with a smartphone and test paper has been developed for the in situ detection of tetracyclines. Abstract : A ratiometric fluorescence method based on carboxylated graphitic carbon nitride nanosheets (C-g-C3 N4 ) and Eu 3+ (C-g-C3 N4 -Eu 3+ ) is described for the detection of tetracyclines (TCs), a broad-spectrum antibiotic. C-g-C3 N4, which was used as a fluorescence enhancer of Eu 3+, was prepared by direct pyrolysis of melamine and post-functionalization. In the presence of TCs, the fluorescence intensity of Eu 3+ at 616 nm increased, accompanied by a decrease of fluorescence intensity of C-g-C3 N4 at 435 nm. Under the optimal conditions, the ratio of fluorescence intensity at 616 nm to the one at 435 nm ( I 616 / I 415 ) increases linearly in the 10 nM to 40 μM TC concentration range with a detection limit of 7.7 nM (S/N = 3). It has been successfully applied in the detection of TCs in spiked tap water and soil samples with satisfactory recovery (96.6–107.2%) and high precision. Furthermore, a test paper and smartphone can assist in rapidly detecting TCs due to the emission color change from blue to red with the addition of TCs. This shows that the proposed method has great potential for the rapid detection TCs in real samples.